Uh-oh: Frances Stark 1991-2015 - Subotnick, Ali 1972- (Delmonico Books, Prestel, 2015)
"This generously illustrated book offers the first comprehensive overview of the work of the Los Angeles-based interdisciplinary artist Frances Stark."
Includes bibliographical references (pages 243-244)
Keywords: Stark, Frances / 1967- / Exhibitions; Stark, Frances -- 1967-; Ausstellungskatalog; Ausstellungskatalog -- Armand Hammer Museum of Art and Cultural Center -- 11.10.2015-24.01.2016 -- Los Angeles, Calif.